Understanding the poor fill factor of solution-processed squaraine based solar cells in terms of charge carrier dynamics probed via impedance and transient spectroscopy. Issue 42 (14th August 2020) - B., Anitha; K. P., Vijith; Alexander, Akhil; Srivastava, Varun; Namboothiry, Manoj A. G.
Abstract : Poor charge transport and extraction along with trap-assisted recombination limit the fill factor of solution processed SQ:PCBM solar cells. Abstract : The charge carrier dynamics that radically affect the performance of solution-processed 2, 4-bis[4-( N, N -diisobutylamino)-2, 6-dihydroxyphenyl]squaraine (DIB SQ):[6, 6]-phenyl-C70-butyric acid methyl ester (PC70 BM) based organic solar cells is analyzed by means of steady-state, impedance and transient spectroscopic techniques. Analysis of current density–voltage characteristics using the modified Shockley diode equation and the light intensity-dependent measurements signifies the contribution of shunt and trap-mediated recombination losses in reducing the fill factor (FF) and efficiency of the SQ based device. Bias voltage-dependent impedance spectra modelled with an equivalent circuit reveal information on the physical processes of charge carrier transport and recombination in the device. Poor charge transport limits the FF of the device, evidenced by the dominance of the resistance corresponding to the charge transport processes over the recombination resistance. Transient photovoltage analysis further confirms the existence of bimolecular and monomolecular recombination in the device. Bias dependent transient photocurrent analysis is performed to probe the charge carrier dynamics at the operating voltages of the device, and it reveals that poor charge extraction due to charge trapping also affects the FF of the device. Furthermore, the morphology of the SQ:PCBM blend film is found to be unfavorable for the smooth extraction and transport of the charge carriers, complementing the findings from steady-state, impedance, and transient measurements.